Bacterial Degradation of Ring-Chlorinated Acetophenones - Higson, Frank K. (1990)
Two strains, Alcaligenes sp. strain ACA and Pseudomonas fluorescens ACB, isolated from acetophenone and 4′-hydroxyacetophenone enrichments, respectively, cometabolize a range of chlorinated acetophenones (CAs). A biological Baeyer-Villiger reaction converts the CA to chlorophenyl acetate. This is evident only in the presence of an esterase inhibitor, since the CA is normally rapidly hydrolyzed to a chlorophenol which has the same substitution pattern as the original ketone. The oxygenase that attacks the ketone uses NADPH in the incorporation of one atom of (18)O(2) and is strongly inhibited by phenols that bear an ortho or meta chlorine or bromine, but much less by cresols or phenol itself. A feedback phenomenon may thus account for the inability of strain ACA to grow on CAs, which also fail to induce the cells for their own metabolism.